2022
DOI: 10.3389/fpubh.2022.1062736
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical trial endpoints of marketed cancer drugs and reimbursement decisions in China

Abstract: ObjectiveThis study aimed to assess whether different clinical trial endpoints in pivotal trials of cancer drugs were associated with reimbursement decisions in China.Materials and methodsCancer drugs marketed before June 30th, 2021 with publicly available technical review reports for application of drug registration on Center for Drug Evaluation (CDE) website were reviewed. The trial design characteristics and relevant clinical outcomes [e.g., overall survival (OS), progression-free survival (PFS) and objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Indeed, most of the indications supported by single-arm clinical trials were approved through conditional approval, which was specialized for the approval of health technology treating serious and life-threatening diseases without available effective treatments. This finding was consistent with the previous study, which concluded that Chinese health authorities have placed a high priority on meeting clinical needs and addressing therapeutic gaps in the NRDL while reducing the requirements for clinical trials [ 33 ]. Nevertheless, extra attention could be paid to addressing the uncertainty of clinical evidence or accounting for the strength of clinical evidence when setting pricing strategies in China.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, most of the indications supported by single-arm clinical trials were approved through conditional approval, which was specialized for the approval of health technology treating serious and life-threatening diseases without available effective treatments. This finding was consistent with the previous study, which concluded that Chinese health authorities have placed a high priority on meeting clinical needs and addressing therapeutic gaps in the NRDL while reducing the requirements for clinical trials [ 33 ]. Nevertheless, extra attention could be paid to addressing the uncertainty of clinical evidence or accounting for the strength of clinical evidence when setting pricing strategies in China.…”
Section: Discussionsupporting
confidence: 92%
“…Because complex patients are simultaneously affected by different conditions, they require multiple diagnostic tests and clinical examinations by various specialists, taking care of the person as a whole rather than just as a sum of different conditions [60]. Policymakers will need to address this when dealing with reimbursement forms, elaborating new schemes that keep this into account, building up a solid and personalized network revolving around each patient, fostering collaborations of medical and nonmedical professionals toward common goals, crossing the borders of academic institutions and national countries, to access the largest amount of information and competencies available [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…We can observe that, concerning the magnitude of OS and PFS gains, high prices might not explicitly yield the equivalent benefit regardless of the implementation of negotiation policy. In fact, to accelerate the launch and access to drugs of treatment shortage in the reimbursement list, policymakers put an increasing emphasis on the clinical consequences or cost-effectiveness of drugs rather than the quality of evidence [ 35 ], resulting in almost a quarter of launched drugs to be approved based on surrogate endpoints rather than the most reliable OS outcome [ 14 ]. Other countries were confronted with the same dilemma [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%